CARDIOVASCULAR CHANGE IN ATHLETES AT DIFFERENT TRAINING STATUS LEVELS - Zhang,Xiumei (2022)
ABSTRACT Introduction: Heart rate and blood pressure are important physiological indicators that reflect cardiovascular function, and they are widely used because they are convenient and practical to measure. Objective: To study the characteristics of cardiovascular changes in athletes under different training conditions. Methods: Thirty-four male students majoring in physical education in universities (group A) and 22 male non-sports majors (group B) with no formal training history were randomly selected. Heart rate before and after exercise and heart rate recovery rate at different stages of the recovery period were compared. Results: As regards heart rate changes in the recovery phase after loading, both groups showed a continuous decline, although the drop in heart rate of group A was slightly lower than that of group B (153.03± 15.88 beats/min, dropped to 110.69± 15.78 beats/minute, 171.00± 14.67 beats/minute dropped to 122. 82± 13.77 beats/min, respectively). However, the heart rate recovery rate of group A (59.40%) was significantly higher than that of group B (49.42%) (P<0.05). Conclusions: Physical exercise plays a significant role in promoting physical fitness and its effect on improving cardiovascular function is especially evident. Level of evidence II; Therapeutic studies - investigation of treatment results.